Saints and villains : a novel - Giardina, Denise, 1951- (New York : W.W. Norton, 1998)
A Protestant minister stands up to the Nazis and pays with his life. The hero is the real-life Pastor Dietrich Bonhoeffer, executed in 1945 for participating in a plot to kill Hitler. The novel describes his youth, his seminary studies in America and his opposition to the Nazis, against whom he did not hesitate to speak out. By the author of The Unquiet Earth.
Keywords: Bonhoeffer, Dietrich, -- 1906-1945 -- Fiction; Good and evil -- Fiction; World War, 1939-1945 -- Germany -- Fiction; Germany -- History -- 1933-1945 -- Fiction; Biographical fiction